Endoprosthesis in the treatment of renovascular hypertension. - Pisco, J M; Branco, J C; Wellenkamp, E; Alpendre, J (Acta Médica Portuguesa, 2001)
Stents were placed in the renal artery in 6 patients, with renal artery stenosis and hypertension, 2 of them had azotemia. The indications were residual stenosis greater than 30% (4 cases) and restenosis following angioplasty (2 cases). The technique and results are described. Cure or improvement of arterial hypertension was obtained in 5 patients and normalization of creatinine in 2 patients with azotemia. We conclude that stent placement improve the immediate and late results of renal angioplasty.